2018
DOI: 10.1007/s10900-018-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Foods That Are Ready-to-Consume (‘Grazing Environments’) Versus Requiring Additional Preparation (‘Grocery Environments’): Implications for Food–Environment Research and Community Health

Abstract: Local businesses that offer foods may create different 'grazing environments' (characterized by sources of ready-to-consume foods) and 'grocery environments' (characterized by source of foods for later preparation). Such environments may be relevant to different populations at different times and may vary by neighborhood. In neighborhoods within two demographically distinct areas of the Bronx, NY [Area A (higher-poverty, greater minority representation, lesser vehicle ownership) vs. Area B], researchers assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…The current study showed that ‘other businesses’ were the segment of a food-environment ‘exposure’ having the greatest growth (compared to general grocers, specialty food stores, and restaurants) and that ‘other businesses’ (34% of the food/drink-source total) rivaled restaurants (35% of the total) as the most prevalent food/drink sources in 2015. Given that other research shows marked differences in the proportion of ‘other businesses’ by neighborhood (and in the proportion selling food/drink), 18,19 failing to consider the contribution of such businesses to food-environment ‘exposures’ could be another source of differential misclassification, bias, false associations, and faulty conclusions in either positive or negative direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study showed that ‘other businesses’ were the segment of a food-environment ‘exposure’ having the greatest growth (compared to general grocers, specialty food stores, and restaurants) and that ‘other businesses’ (34% of the food/drink-source total) rivaled restaurants (35% of the total) as the most prevalent food/drink sources in 2015. Given that other research shows marked differences in the proportion of ‘other businesses’ by neighborhood (and in the proportion selling food/drink), 18,19 failing to consider the contribution of such businesses to food-environment ‘exposures’ could be another source of differential misclassification, bias, false associations, and faulty conclusions in either positive or negative direction.…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, we conducted a broad assessment of all storefront businesses that might contribute to an urban food environment at two points in time. Having completed an initial assessment in the Bronx, NY five years earlier 17 and subsequent assessments in surrounding neighborhood since, 1824 we had observed some changes on Bronx streets that seemed to suggest increasing food/drink availability (e.g., new storefronts opening and existing storefronts starting to offer food/drink items). We hypothesized that food/drink would be available from more places on more streets at the time of our subsequent assessment than at the time of our initial assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The principal investigator, having conducted earlier food-environment assessments, 1922 including studies using REDCap, 23,29 trained other members of the research team in data collection procedures. Three team members practiced procedures by observing 20 storefront businesses outside of the study area—first independently, then as a group.…”
Section: Methodsmentioning
confidence: 99%
“…2530 Such businesses, or “other storefront businesses” (OSBs) may not primarily focus on selling food but can account for as much as a third of all storefront food options in a community. 2931 Food-selling OSBs can be comparable in number to restaurants and greater in number than so-called “food stores.” 31…”
Section: Storefronts Beyond Food Stores and Restaurantsmentioning
confidence: 99%
“…Food-selling OSBs almost all offer unhealthful items (e.g., chips, cookies, soda), yet only about 10% offer such items exclusively. 29,30 More-healthful options (e.g. dried fruits, whole-grain snacks, nuts) might be made more available in OSBs through approaches tested in other settings; for example, targeting their vending machines, 32,33 checkouts, 3436 or broader inventories more generally.…”
Section: Storefronts Beyond Food Stores and Restaurantsmentioning
confidence: 99%